A Review of Neuroprotective Effects and Mechanisms of Ginsenosides From Panax Ginseng in Treating Ischemic Stroke - Zhao, Aimei; Liu, Nan; Yao, Mingjiang; Zhang, Yehao; Yao, Zengyu; Feng, Yujing; Liu, Jianxun; Zhou, Guoping (Frontiers in Pharmacology, 2022)
Ischemic stroke has been considered one of the leading causes of mortality and disability worldwide, associated with a series of complex pathophysiological processes. However, effective therapeutic methods for ischemic stroke are still limited. Panax ginseng, a valuable traditional Chinese medicine, has been long used in eastern countries for various diseases. Ginsenosides, the main active ingredient of Panax ginseng, has demonstrated neuroprotective effects on ischemic stroke injury during the last decade. In this article, we summarized the pathophysiology of ischemic stroke and reviewed the literature on ginsenosides studies in preclinical and clinical ischemic stroke. Available findings showed that both major ginsenosides and minor ginsenosides (such as Rg3, Rg5, and Rh2) has a potential neuroprotective effect, mainly through attenuating the excitotoxicity, Ca2+ overload, mitochondria dysfunction, blood-brain barrier (BBB) permeability, anti-inflammation, anti-oxidative, anti-apoptosis, anti-pyroptosis, anti-autophagy, improving angiogenesis, and neurogenesis. Therefore, this review brings a current understanding of the mechanisms of ginsenosides in the treatment of ischemic stroke. Further studies, especially in clinical trials, will be important to confirm the clinical value of ginseng and ginsenosides.